(untitled) (Historia, 2021)
Dr. H.F. Verwoerd's Dutch descent: his Achilles heel? In the study attention is given to the Dutch roots of Dr. H.F. Verwoerd. There is an attempt at giving a perception of the contemporary resception of the former premier of South Africa in the public sphere. Attention is also given to the effect his Ditch roots might have had on the political leader of the twentieth century who was directly responsible for the implementation of the apartheid policy.